(untitled) (PerCursos, 2021)
This article aims to propose points of contact between the experiences of violence and memory production in the context of Argentina and Palestine, based on the analysis of two different works, an autobiographical book written by the Palestinian Ibtisam Barakat and a memoir produced by a collective of children of Argentine repressors. Starting from different fields, the sources have a common analytical potential: women’s contemporary writing, with narrative forms and relatable thematic concerns. Reflections are proposed on the analyzed works, considering two main objectives: how the “postmemory” can be a relevant category for thinking about these historical processes, based on a bibliographic review of the concept that tests it in marginal scenarios, and to conjecture about the place of female autofiction in the production of the recent past. Understanding postmemory as a critical device and in view of the temporal complexity that the Argentine and Palestinian cases raise, the use of the category can be an analytical possibility for the entanglement of memories reflected in these texts, despite the particularities of the effects of violence of State for each case.